Which bank is the central bank? An application of Markov theory to the Canadian large value transfer system - Morten Bech; James T. E. Chapman; Rod Garratt (Bank of Canada, 2008)
We use a method similar to Google's PageRank procedure to rank banks in the Canadian Large Value Transfer System (LVTS). Along the way we obtain estimates of the payment processing speeds for the individual banks. These differences in processing speeds are essential for explaining why observed daily distributions of liquidity differ from the initial distributions, which are determined by the credit limits selected by banks.
Keywords: C11; E50; G20; 330; C11; E50; G20; Bank; Zentralbank; Bankbilanz; Bankenliquidität; Ranking-Verfahren; Kanada